Model Komunikasi Pembelajaran Pendidikan Agama Islam Pada Anak Berkebutuhan Khusus Di Sekolah Luar Biasa Dharma Hafiz Pringgabaya Utara - Shanti Ariani, Sri (Lembaga Bale Literasi, 2024)
This study examines the communication model for Islamic Religious Education learning for children with special needs at the Dharma Hafiz Special Needs School in North Pringgabaya.This study is qualitative, with data collection techniques using literature review, observation, interviews, and documentation. The results of this study indicate that: 1) in Islamic Religious Education learning, the characteristics of children with special needs (ABK) participating in Islamic Religious Education (PAI) at the Dharma Hafiz Special Needs School in North Pringgabaya include varied learning styles, each guided by their own teacher. They often use a systematic approach, are not allowed to be left alone and learn independently, and require supervision to ensure children's successful participation in PAI learning, such as literacy/Quranic learning, where the material provided varies, for example, reading short surahs, practicing ablution, and practicing prayer. 2) The communication model used by teachers in effective Islamic Religious Education learning and the communication system where the blind person uses mobility orientation (OM) white cane, tusing, recording device, the deaf person uses sign language or body language, the mentally retarded person uses exercise and self-development, the physically disabled person uses binagerak, exercise and self-development, the autism person uses routine training and behavioral changes. So, in communication between teachers and students at SLB Dharma Hafiz Pringgabaya Utara, there are actions taken by teachers when communicating with students that vary according to the psychological condition of their students and convey stimuli, words to change their students' behavior and explain using communication models according to the conditions of children with special needs so that the objectives of a teaching and learning process can be implemented well. 3) Obstacles to learning Islamic Religious Education for children with special needs at SLB Dharma Hafiz Pringgabaya Utara, namely in the learning activities, students do not easily participate in learning, students need to approach teachers in following learning, ordinary students expect gifts to facilitate learning. The solution to address these issues is to foster good collaboration between students, teachers, administrative staff, and the principal, as well as the availability/readiness of existing facilities and infrastructure.